Silica Coating of Nonsilicate Nanoparticles for Resin-Based Composite Materials. (November 2016) - Kaizer, M.R.; Almeida, J.R.; Gonçalves, A.P.R.; Zhang, Y.; Cava, S.S.; Moraes, R.R.
This study was designed to develop and characterize a silica-coating method for crystalline nonsilicate ceramic nanoparticles (Al2 O3, TiO2, and ZrO2 ). The hypothesis was that the coated nonsilicate nanoparticles would stably reinforce a polymeric matrix due to effective silanation. Silica coating was applied via a sol-gel method, with tetraethyl orthosilicate as a silica precursor, followed by heat treatment. The chemical and microstructural characteristics of the nanopowders were evaluated before and after silica coating through x-ray diffraction, BET (Brunauer-Emmett-Teller), energy-dispersive x-ray spectroscopy, field emission scanning electron microscopy, and transmission electron microscopy analyses. Coated and noncoated nanoparticles were silanated before preparation of hybrid composites, which contained glass microparticles in addition to the nanoparticles. The composites were mechanically tested in 4-point bending mode after aging (10, 000 thermal cycles). Results of all chemical and microstructural analyses confirmed the successful obtaining of silica-coated nanoparticles. Two distinct aspects were observed depending on the type of nanoparticle tested: 1) formation of a silica shell on the surface of the particles and 2) nanoparticle clusters embedded into a silica matrix. The aged hybrid composites formulated with the coated nanoparticles showed improved flexural strength (10% to 30% higher) and work of fracture (35% to 40% higher) as compared with composites formulated with noncoated nanoparticles. The tested hypothesis was confirmed: silanated silica-coated nonsilicate nanoparticles yielded stable reinforcement of dimethacrylate polymeric matrix due to effective silanation. The silica-coating method presented here is a versatile and promising novel strategy for the use of crystalline nonsilicate ceramics as a reinforcing phase of polymeric composite biomaterials.